PENGARUH LIKUIDITAS, SALES GROWTH DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS - Beby Ratna Sari; Dirvi Surya Abbas; Hesty Ervianni Zulaecha; Imas Kismanah (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2022)
Every company that stands and exists in the business world is to get profit, another important thing is to survive in the business world. Many things and obstacles are often faced by a company to maintain its existence. Therefore the researchers conducted this research with the aim to determine the effect of liquidity, sales growth and company size on financial distress. The method used in this research is panel data Regression data management, with Eviews 12 as a data processing tool. The data collection technique itself uses purposive sampling and the data used is secondary data. The population of this study are consumer industry companies listed on the IDX in 2017-2022. The results of this study are that liquidity and company size have an insignificant positive effect and sales growth has an insignificant negative effect on financial distress.